Increased uptake of the P2X7 receptor radiotracer 18F‐JNJ‐64413739 in the brain and peripheral organs according to the severity of status epilepticus in male mice. Issue 2 (27th December 2022) - Morgan, James; Moreno, Oscar; Alves, Mariana; Baz, Zuriñe; Menéndez Méndez, Aida; Leister, Hanna; Melia, Ciara; Smith, Jonathon; Visekruna, Alexander; Nicke, Annette; Bhattacharya, Anindya; Ceusters, Marc; et al.
Abstract: Objective: The P2X7 receptor (P2X7R) is an important contributor to neuroinflammation, responding to extracellularly released adenosine triphosphate. Expression of the P2X7R is increased in the brain in experimental and human epilepsy, and genetic or pharmacologic targeting of the receptor can reduce seizure frequency and severity in preclinical models. Experimentally induced seizures also increase levels of the P2X7R in blood. Here, we tested 18 F‐JNJ‐64413739, a positron emission tomography (PET) P2X7R antagonist, as a potential noninvasive biomarker of seizure‐damage and epileptogenesis. Methods: Status epilepticus was induced via an intra‐amygdala microinjection of kainic acid. Static PET studies (30 min duration, initiated 30 min after tracer administration) were conducted 48 h after status epilepticus via an intravenous injection of 18 F‐JNJ‐64413739. PET images were coregistered with a brain magnetic resonance imaging atlas, tracer uptake was determined in the different brain regions and peripheral organs, and values were correlated to seizure severity during status epilepticus. 18 F‐JNJ‐64413739 was also applied to ex vivo human brain slices obtained following surgical resection for intractable temporal lobe epilepsy. Results: P2X7R radiotracer uptake correlated strongly with seizure severity during status epilepticus in brain structures including the cerebellum and ipsi‐ and contralateral cortex, hippocampus, striatum, and thalamus. In addition, a correlation between radiotracer uptake and seizure severity was also evident in peripheral organs such as the heart and the liver. Finally, P2X7R radiotracer uptake was found elevated in brain sections from patients with temporal lobe epilepsy when compared to control. Significance: Taken together, our data suggest that P2X7R‐based PET imaging may help to identify seizure‐induced neuropathology and temporal lobe epilepsy patients with increased P2X7R levels possibly benefitting from P2X7R‐based treatments.